State and Religion - Barker, Renae, author.
1 online resource (354 pages)
Keywords: With its increasingly secular and religiously diverse population Australia faces many challenges in determining how the state and religion should interact. Australia is not unique in facing these challenges. States worldwide, including common law countries with shared legal and religious heritages, have also been faced with the question of how the state and religion should relate to one another. Countries such as the United Kingdom, Canada, New Zealand and the United States have all had to grapple with how to manage the state-religion relationship in the present day.This book provides a comprehensive historical review of the interaction of the state and religion in Australia. It brings together multiple examples of areas in which the state and religion interact, and reviews these examples across Australia’s history from settlement through to present day. The book sets this story within a wider theoretical context via an examination of theories of state-religion relationships as well as a comparison with other similar common law jurisdictions. The book demonstrates how the solutions arrived at in Australia is uniquely Australian owing to Australia’s unique legal system, religious demographics and history. However this is just one possible outcome among many that have been tried in common law liberal democracies.